Achieving carbon neutrality: How does the construction of national high-tech zones affect the green innovation of enterprises? Based on quasi-natural experiments in pilot areas in China - Liu, Baoliu; Jin, Xin; Zhao, Pu; Li, Zhou; Xia, Jing (Frontiers in Ecology and Evolution, 2023)
From the standpoint of green patents, verifying the influence of the construction of national high-tech zones on the degree of green innovation of enterprises is of enormous theoretical and practical importance. This study constructs a multi-period two-difference model using micro-enterprise panel data from Chinese A-share listed enterprises to assess the influence of the national high-tech zone policy's implementation on enterprises' levels of green innovation. The outcomes of the study show that: first, the establishment of national high-tech zones greatly increases the level of green innovation among enterprises. While the effect on green and practical patents is average, the effect on green invention patents is more obvious. Second, how enterprises in national high-tech zones promote green innovation varies significantly. Promotional effects are more prominent in Tier 1 and Tier 2 regions, non-state firms, and high-tech industries with significant economic development. State-owned enterprises, non-high-tech industries, and third-tier and lower-tier regions, on the other hand, fared brilliantly. Third, additional action mechanisms show that the establishment of national high-tech zones can contribute to the institutional environmental effects of enterprises and the concentration of green innovation elements, thereby realizing regional green innovation development and improving the level of green operation. Thus, our research provides an empirical foundation for stimulating the formation of national high-tech zones, increasing firms' ability to innovate on their own, and nurturing the long-term growth of national high-tech zones and associated businesses.